Transforming Turbulent Fluid Flow Equations Batik Patterns Based On Mathematical Visualizations - Alifa Ulayya; Najwa Azra Nadifa; Aulia Sardillah Ramadhani; Sugiyanto (Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2026)
This study explores the transformation of turbulent fluid flow equations into visual patterns that can be developed into batik motifs based on mathematical visualization. The research is grounded in fluid mechanics, particularly the Navier–Stokes equations, which are simplified using the Reynolds-Averaged Navier–Stokes (RANS) approach and further represented through a two-dimensional velocity field. The resulting mathematical models are visualized using GeoGebra, producing repeating circular patterns and spiral curves. These patterns are then developed through visual transformations such as repetition, reflection, and rotation to create structured and aesthetically appealing designs. The results show that mathematical representations of turbulent flow can generate patterns that align with the principles of batik, including balance, symmetry, and repetition. Furthermore, the study highlights the philosophical meanings embedded in the patterns, where circular motifs symbolize balance and unity, while spiral motifs represent growth and dynamic change. This research demonstrates the integration of mathematics, technology, and cultural art, providing an innovative approach to batik motif creation while preserving cultural values.